2015
DOI: 10.1002/2015wr017139
|View full text |Cite
|
Sign up to set email alerts
|

Catchment‐scale Richards equation‐based modeling of evapotranspiration via boundary condition switching and root water uptake schemes

Abstract: In arid and semiarid climate catchments, where annual evapotranspiration (ET) and rainfall are typically comparable, modeling ET is important for proper assessment of water availability and sustainable land use management. The aim of the present study is to assess different parsimonious schemes for representing ET in a process-based model of coupled surface and subsurface flow. A simplified method for computing ET based on a switching procedure for the boundary conditions of the Richards equation at the soil s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 53 publications
2
24
0
Order By: Relevance
“…Yang et al (2016) demonstrated that the rooting depth of vegetation influenced continental water balances globally, though this effect was estimated through the simplified model of Donohue et al (2012), which lacks a mechanistic foundation. Camporese et al (2015) reached similar conclusions with a physically based subsurface model applied to a water-limited catchment in southern Australia. Our research suggests that functional RWU strategies influence catchment transpiration (Figure 4a) particularly in northern forests (Figures 3a and 3c) during the growing season (Figure 4c), highlighting the conditional sensitivity of catchment-scale water and energy balances to forest rooting strategies.…”
Section: Rwu Control Of Catchment Etsupporting
confidence: 70%
“…Yang et al (2016) demonstrated that the rooting depth of vegetation influenced continental water balances globally, though this effect was estimated through the simplified model of Donohue et al (2012), which lacks a mechanistic foundation. Camporese et al (2015) reached similar conclusions with a physically based subsurface model applied to a water-limited catchment in southern Australia. Our research suggests that functional RWU strategies influence catchment transpiration (Figure 4a) particularly in northern forests (Figures 3a and 3c) during the growing season (Figure 4c), highlighting the conditional sensitivity of catchment-scale water and energy balances to forest rooting strategies.…”
Section: Rwu Control Of Catchment Etsupporting
confidence: 70%
“…Actual evapotranspiration ( ET a ) is computed using a sink term ( S ) in the Richards equation to account for root water uptake, as in Camporese et al . []. Potential transpiration is distributed across the root depth as a function of the root distribution, β , which is expressed as: βtrue(ztrue)=true[1zzmtrue]epzzmz, where z is depth (i.e., positive downward), z m is the maximum rooting depth, and p z is an empirical shape parameter [ Vrugt et al ., ].…”
Section: Methodsmentioning
confidence: 99%
“…Root water uptake compensatory mechanisms were not included here, contrasting with Camporese et al . [].…”
Section: Methodsmentioning
confidence: 99%
“…The data set was divided into three parts for warm-up ( The parameters listed in Table 1 were varied in the sensitivity analysis (Camporese et al, 2010;Camporese et al, 2014;Camporese et al, 2015). Each of the parameters was increased and decreased by 20% of their initial value, whereas the other parameters remained unchanged.…”
Section: Model Setupmentioning
confidence: 99%
“…A number of studies modelled intermittent catchments (e.g., Ye et al, 1997;Ye et al, 1998;O'Toole et al, 2018;Risva et al, 2018) using lumped models because of low data requirements, simplicity of application, and ability of simulation at short timescales (Ivkovic et al, 2009). Integrated surface-subsurface hydrological models (ISSHMs) have recently received increasing attention in modelling intermittent catchments (e.g., Saber et al, 2015;Camporese et al, 2015;Dean et al, 2016;Maref & Seddini, 2018). Conversely, detailed hydrological modelling of natural catchments requires dealing with complex topography and geology, multiple nonlinear dynamics, and heterogeneous parameters (Gauthier et al, 2009;Fatichi et al, 2016).…”
mentioning
confidence: 99%